Operation valentine - Hill, Loretta (North Sydney, NSW : Penguin Random House Australia, 2014)
From the author of the bestselling The Girl in Steel-Capped Boots and One Little White Lie, comes a laugh-out-loud romantic comedy about dating in the modern world. "Once upon a time, there was a young girl called Sarah Dubert who needed to fall in love in six weeks . . ." Thanks to food poisoning, broken dates, airport malfunctions and even death, Sarah Dubert has never had a boyfriend on Valentine's Day. However this year she's determined to break the curse and snare herself a man before Big V. Signing herself up to the online dating site soulmates.com, she begins eliminating possible candidates through dates at her favourite bar, The Blue Saloon . . . Owen Black, the handsome new owner of The Blue Saloon, likes his women fast, experienced and temporary. A woman on a mission to find love - particularly one with a six-week deadline - would normally have him running for the hills. So why is he so uncharacteristically interested in Sarah's search? And, more importantly, the success of her dates.?.
Imprint: RHA eBooks Adult.
Audience: General.
Vendor-supplied metadata
Keywords: Romance fiction; Valentine's Day -- Fiction; Saint-Valentin (Fête) -- Romans, nouvelles, etc; Fiction - Romance - General; Romance fiction; Romance; Valentine's Day; Australian; Electronic books; Fiction